2021
DOI: 10.1186/s13033-020-00427-x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and drivers to service delivery in global mental health projects

Abstract: Background Research in global mental health (GMH) has previously documented how contextual factors like political instability, poverty and poorly-funded health infrastructure continue to compromise effective and equitable mental health service delivery. There is a need to develop more feasible and evidence-based solutions through implementation research. This paper, one in a series pertaining to implementation in GMH projects worldwide, focuses on implementation factors influencing mental healt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Initiatives also reported critical funding situations threatening their sustainability, which could not always be resolved within the 1-year partnership period. These reports resonate with other accounts of global mental health projects operating in low-resource settings 27 and highlight the strain that underinvestment in mental health-a widely recognised issue since the field's early days 29 -places on those working on the ground. Expanding investment into CBMHIs across diverse contexts 30 must be accompanied by longer funding cycles and further diversification of the mechanisms by which funding is currently granted.…”
Section: Transform Funding Mechanismssupporting
confidence: 64%
See 1 more Smart Citation
“…Initiatives also reported critical funding situations threatening their sustainability, which could not always be resolved within the 1-year partnership period. These reports resonate with other accounts of global mental health projects operating in low-resource settings 27 and highlight the strain that underinvestment in mental health-a widely recognised issue since the field's early days 29 -places on those working on the ground. Expanding investment into CBMHIs across diverse contexts 30 must be accompanied by longer funding cycles and further diversification of the mechanisms by which funding is currently granted.…”
Section: Transform Funding Mechanismssupporting
confidence: 64%
“…27 Initiatives also appreciated the relationships forged with other organisations from the Ember cohort and gaining access to broader global mental health networks. Fostering collaboration within this field, including opportunities for conversation and knowledge exchange between organisations, should be an immediate priority for funders to support initiatives to thrive.…”
mentioning
confidence: 99%
“…Besides, although partner support facilitated integration, it was observed that this support might be unsustainable. Several studies have revealed similar challenges of sustainability of interventions due to donor driven projects [32][33][34][35]. This implies that sustained implementation of nutrition interventions requires reasonable nancial contribution from government.…”
Section: Integration In Support Systemmentioning
confidence: 99%
“…In LMICs the increasing burden of cancer further strains struggling health care systems 1 and mental health service delivery is significantly limited by fragmented health systems, lack of highly-skilled practitioners, and inadequate resources for highly complex psychological interventions. 15 Thus, in LMICs there is an even greater need for psycho-oncological interventions that are evidence-based, low intensity, and widely and freely available. 16 The aim of this study was to examine the feasibility and acceptability of WET among Iranian women with breast cancer and cancer-related PTSD.…”
Section: Introductionmentioning
confidence: 99%